Sosial Media Sebagai Strategi Untuk Meningkatkan Branding Kelompok Tani Maju 01 - Nugroho, Taufik Rizal Dwi Adi; Shah, Aulia Kafi Yugi; Noer, Era Vanessa (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The Farmer Group